EFFECTIVENESS OF AI-GENERATED LISTENING MATERIALS VS. TEXTBOOK AUDIO IN EFL LEARNING - Baxramova Malika Muzaffarovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study examines the comparative effectiveness of AI-generated listening materials and traditional textbook audio in the context of English as a Foreign Language (EFL) learning. With the growing use of Artificial Intelligence in language education, learners are increasingly exposed to dynamic, customizable, and context- specific audio content generated by advanced text-to-speech technologies. This article analyzes how such AI-driven resources impact listening comprehension, learner engagement, and pedagogical flexibility compared to scripted, professionally recorded textbook audio. Drawing on theoretical perspectives and recent empirical findings, the paper explores dimensions such as adaptability, content authenticity, listening accuracy, and learner motivation. While AI-generated materials offer greater personalization and relevance to real-world communication, textbook audio provides structured, predictable input that aligns closely with curriculum goals. The findings suggest that a blended model combining both modalities may yield optimal results, balancing innovation with pedagogical consistency. The study highlights the importance of integrating technological advancements thoughtfully to enhance listening proficiency while supporting diverse learner needs and preferences.